The Role of financial sector in the economic development of ethiopia - Kydaki, Gezahegn Baismak (KDI School, 2000)
Since the Debt Crisis of 1982 and rapid Voluntary capital inflow restriction to the developing countries, the financial liberalization models increasingly dominant policy advocated by the IMF and the World Bank. Today, it is a conventional wisdom that financial liberalization is the most efficient way for the financial sector and overall economic growth. Thus, the study seeks to make comparative study of the performance of the financial sector before and after the economic reform of Ethiopia. Thus, the paper is divided into five chapters. The first chapter concerned with introductory part. All the technical questions related to the study such as problem statement, objective of the study, methodology and scope of the study are discussed in this section. The second chapter reviews the literatures that related to this study. Chapter three concentrates on overall review of the Ethiopian economy in different periods. The fourth chapter is the core of the study that receives a wide coverage in the literature. Finally, the fifth chapter concludes the study and recommends a policy on the bases of the findings.
Thesis(Master) --KDI School:Master of Public Policy,2000